A place called home : school-university-community collaboration and the immigrant educational experience - Reardon, R. Martin; Leonard, Jack, 1948- (Current perspectives on school/university/community research., 2021)
"Describing global trends in forced displacement in 2019, Filippo Grandi, United Nations High Commissioner for Refugees declared that "we are witnessing a changed reality in that forced displacement is not only vastly more widespread but it simply no longer a short-term and temporary phenomenon" (https://www.unhcr.org/globaltrends2019/). At the end of 2019, almost 80 million people had been forced to leave the place they called home "as a result of persecution, conflict, violence, human rights violations or events seriously disturbing public order," according to the United Nations High Commission for Refugees (https://www.unhcr.org/globaltrends2019/). This volume presents the concerted efforts of chapter contributors to alleviate the alienation of those who have been displaced and help them to feel at home in the country in which they have sought refuge. Chapter contributors highlight their endeavors specifically with Latino, Hmong, and African immigrants in the United States and Canada, as well as with a veritable united nations of immigrant identities in general. Endeavors oriented to making immigrants feel at home inevitably raise the vexed question of what it means to be a good member of a society-regardless of whether one is a citizen"--